Vaccines for the 21st Century: A Tool for Decisionmaking - Institute of Medicine (The National Academies Press, 2000)
Vaccines have made it possible to eradicate the scourge of smallpox, promise the same for polio, and have profoundly reduced the threat posed by other diseases such as whooping cough, measles, and meningitis. What is next? There are many pathogens, autoimmune diseases, and cancers that may be promising targets for vaccine research and development. This volume provides an analytic framework and quantitative model for evaluating disease conditions that can be applied by those setting priorities for vaccine development over the coming decades. The committee describes an approach for comparing potential new vaccines based on their impact on morbidity and mortality and on the costs of both health care and vaccine development. The book examines: Lessons to be learned from the polio experience. Scientific advances that set the stage for new vaccines. Factors that affect how vaccines are used in the population. Value judgments and ethical questions raised by comparison of health needs and benefits. The committee provides a way to compare different forms of illness and set vaccine priorities without assigning a monetary value to lives. Their recommendations will be important to anyone involved in science policy and public health planning: policymakers, regulators, health care providers, vaccine manufacturers, and researchers.

Eliminating the Public Health Problem of Hepatitis B and C in the United States: Phase One Report - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2016)
Hepatitis B and C cause most cases of hepatitis in the United States and the world. The two diseases account for about a million deaths a year and 78 percent of world's hepatocellular carcinoma and more than half of all fatal cirrhosis. In 2013 viral hepatitis, of which hepatitis B virus (HBV) and hepatitis C virus (HCV) are the most common types, surpassed HIV and AIDS to become the seventh leading cause of death worldwide. The world now has the tools to prevent hepatitis B and cure hepatitis C. Perfect vaccination could eradicate HBV, but it would take two generations at least. In the meantime, there is no cure for the millions of people already infected. Conversely, there is no vaccine for HCV, but new direct-acting antivirals can cure 95 percent of chronic infections, though these drugs are unlikely to reach all chronically-infected people anytime soon. This report, the first of two, examines the feasibility of hepatitis B and C elimination in the United States and identifies critical success factors. The phase two report will outline a strategy for meeting the elimination goals discussed in this report.

Hepatitis and Liver Cancer: A National Strategy for Prevention and Control of Hepatitis B and C - Institute of Medicine (The National Academies Press, 2010)
The global epidemic of hepatitis B and C is a serious public health problem. Hepatitis B and C are the major causes of chronic liver disease and liver cancer in the world. In the next 10 years, 150,000 people in the United States will die from liver disease or liver cancer associated with chronic hepatitis B virus (HBV) or hepatitis C virus (HCV) infections. Today, between 800,000 and 1.4 million people in the United States have chronic hepatitis B and between 2.7 and 3.9 million have chronic hepatitis C. People most at risk for hepatitis B and C often are the least likely to have access to medical services. Reducing the rates of illness and death associated with these diseases will require greater awareness and knowledge among health care workers, improved identification of at-risk people, and improved access to medical care. Hepatitis B is a vaccine-preventable disease. Although federal public health officials recommend that all newborns, children, and at-risk adults receive the vaccine, about 46,000 new acute cases of the HBV infection emerge each year, including 1,000 in infants who acquire the infection during birth from their HBV-positive mothers. Unfortunately, there is no vaccine for hepatitis C, which is transmitted by direct exposure to infectious blood. Hepatitis and Liver Cancer identifies missed opportunities related to the prevention and control of HBV and HCV infections. The book presents ways to reduce the numbers of new HBV and HCV infections and the morbidity and mortality related to chronic viral hepatitis. It identifies priorities for research, policy, and action geared toward federal, state, and local public health officials, stakeholder, and advocacy groups and professional organizations.

Priorities for the National Vaccine Plan - Institute of Medicine (The National Academies Press, 2010)
Vaccination is a fundamental component of preventive medicine and public health. The use of vaccines to prevent infectious diseases has resulted in dramatic decreases in disease, disability, and death in the United States and around the world. The current political, economic, and social environment presents both opportunities for and challenges to strengthening the U.S. system for developing, manufacturing, regulating, distributing, funding, and administering safe and effective vaccines for all people. Priorities for the National Vaccine Plan examines the extraordinarily complex vaccine enterprise, from research and development of new vaccines to financing and reimbursement of immunization services. Priorities for the National Vaccine Plan examines the extraordinarily complex vaccine enterprise, from research and development of new vaccines to financing and reimbursement of immunization services. The book makes recommendations about priority actions in the update to the National Vaccine Plan that are intended to achieve the objectives of disease prevention and enhancement of vaccine safety. It is centered on the plan's five goals in the areas of vaccine development, safety, communication, supply and use, and global health.

Adverse Effects of Pertussis and Rubella Vaccines - Institute of Medicine (The National Academies Press, 1991)
Parents have come to depend on vaccines to protect their children from a variety of diseases. Some evidence suggests, however, that vaccination against pertussis (whooping cough) and rubella (German measles) is, in a small number of cases, associated with increased risk of serious illness. This book examines the controversy over the evidence and offers a comprehensively documented assessment of the risk of illness following immunization with vaccines against pertussis and rubella. Based on extensive review of the evidence from epidemiologic studies, case histories, studies in animals, and other sources of information, the book examines: The relation of pertussis vaccines to a number of serious adverse events, including encephalopathy and other central nervous system disorders, sudden infant death syndrome, autism, Guillain-Barre syndrome, learning disabilities, and Reye syndrome. The relation of rubella vaccines to arthritis, various neuropathies, and thrombocytopenic purpura. The volume, which includes a description of the committee's methods for evaluating evidence and directions for future research, will be important reading for public health officials, pediatricians, researchers, and concerned parents.

Immunization Safety Review: Measles-Mumps-Rubella Vaccine and Autism - Institute of Medicine (The National Academies Press, 2001)
Immunization is widely regarded as one of the most effective and beneficial tools for protecting the public's health. In the United States, immunization programs have resulted in the eradication of smallpox, the elimination of polio, and the control and near elimination of once-common, often debilitating and potentially life-threatening diseases, including measles, mumps, rubella, diphtheria, pertussis, tetanus, and Haemophilus influenza type b. Along with the benefits of widespread immunization, however, have come concerns about the safety of vaccines. No vaccine is perfectly safe or effective, and vaccines may lead to serious adverse effects in some instances. Furthermore, if a serious illness is observed after vaccination, it is often unclear whether that sequence is coincidental or causal, and it can be difficult to determine the true nature of the relationship, if any, between the vaccination and the illness. Ironically, the successes of vaccine coverage in the United States have made it more difficult for the public to weigh the benefits and complications of vaccines because the now-controlled diseases and their often-serious risks are no longer familiar. However, because vaccines are so widely used-and because state laws require that children be vaccinated before entering daycare and school, in part to protect others-it is essential that safety concerns be fully and carefully studied. Immunization Safety Review: Measles-Mumps-Rubella Vaccine and Autism, the first of a series from the Institute of Medicine (IOM) Immunization Safety Review Committee, presents an assessment of the evidence regarding a hypothesized causal association between the measles-mumps-rubella (MMR) vaccine and autism, an assessment of the broader significance for society of the issues surrounding the MMR-autism hypothesis, and the committee's conclusions and recommendations based on those assessments.

Ending Neglect: The Elimination of Tuberculosis in the United States - Institute of Medicine (The National Academies Press, 2000)
Tuberculosis emerged as an epidemic in the 1600s, began to decline as sanitation improved in the 19th century, and retreated further when effective therapy was developed in the 1950s. TB was virtually forgotten until a recent resurgence in the U.S. and around the world2014ominously, in forms resistant to commonly used medicines. What must the nation do to eliminate TB? The distinguished committee from the Institute of Medicine offers recommendations in the key areas of epidemiology and prevention, diagnosis and treatment, funding and organization of public initiatives, and the U.S. role worldwide. The panel also focuses on how to mobilize policy makers and the public to effective action. The book provides important background on the pathology of tuberculosis, its history and status in the U.S., and the public and private response. The committee explains how the U.S. can act with both self-interest and humanitarianism in addressing the worldwide incidence of TB.

Immunization Safety Review: Thimerosal-Containing Vaccines and Neurodevelopmental Disorders - Institute of Medicine (The National Academies Press, 2001)
In this report, the Immunization Safety Review committee examines the hypothesis of whether or not the use of vaccines containing the preservative thimerosal can cause neurodevelopmental disorders (NDDs), specifically autism, attention deficit\/hyperactivity disorder (ADHD), and speech or language delay.

Vaccine Safety Research, Data Access, and Public Trust - Institute of Medicine (The National Academies Press, 2005)
The Vaccine Safety Datalink (VSD) is a large, linked database of patient information that was developed jointly by CDC and several private managed care organizations in 1991. It includes data on vaccination histories, health outcomes, and characteristics of more than 7 million patients of eight participating health organizations. Researchers from CDC and the managed care groups have used VSD information to study whether health problems are associated with vaccinations. The subsequent VSD data sharing program was launched in 2002 to allow independent, external researchers access to information in the database. In this report, the committee that was asked to review aspects of this program recommends that two new oversight groups are needed to ensure that the policies and procedures of the VSD and its data sharing program are implemented as fairly and openly as possible.

Calling the Shots: Immunization Finance Policies and Practices - Institute of Medicine
Calling the Shots examines the basic strategies that finance the national immunization system in the current health care climate. It is a comprehensive volume, rich with data and highlighted examples, that explores: The evolution of the system in light of changing U.S. demographics, development of new vaccines, and other factors. The effectiveness of public health and health insurance strategies, with special emphasis on the performance of the \

The Domestic and International Impacts of the 2009-H1N1 Influenza A Pandemic: Global Challenges, Global Solutions: Workshop Summary - Institute of Medicine
In March and early April 2009, a new, swine-origin 2009-H1N1 influenza A virus emerged in Mexico and the United States. During the first few weeks of surveillance, the virus spread by human-to-human transmission worldwide to over 30 countries. On June 11, 2009, the World Health Organization (WHO) raised the worldwide pandemic alert level to Phase 6 in response to the ongoing global spread of the novel influenza A (H1N1) virus. By October 30, 2009, the H1N1 influenza A had spread to 191 countries and resulted in 5,700 fatalities. A national emergency was declared in the United States and the swine flu joined SARS and the avian flu as pandemics of the 21st century. Vaccination is currently available, but in limited supply, and with a 60 percent effectiveness rate against the virus. The story of how this new influenza virus spread out of Mexico to other parts of North America and then on to Europe, the Far East, and now Australia and the Pacific Rim countries has its origins in the global interconnectedness of travel, trade, and tourism. Given the rapid spread of the virus, the international scientific, public health, security, and policy communities had to mobilize quickly to characterize this unique virus and address its potential effects. The World Health Organization and Centers for Disease Control have played critical roles in the surveillance, detection and responses to the H1N1 virus. The Domestic and International Impacts of the 2009-H1N1 Influenza A Pandemic: Global Challenges, Global Solutions aimed to examine the evolutionary origins of the H1N1 virus and evaluate its potential public health and socioeconomic consequences, while monitoring and mitigating the impact of a fast-moving pandemic. The rapporteurs for this workshop reported on the need for increased and geographically robust global influenza vaccine production capacities; enhanced and sustained interpandemic demand for seasonal influenza vaccines; clear \